Metabolic Syndrome and Mortality in Continuous Ambulatory Peritoneal Dialysis Patients: A 5-Year Prospective Cohort Study - WenLong Gu; Chunyan Yi; Xueqing Yu; Xiao Yang (Karger Publishers, 2019)
Background/Aims: Metabolic syndrome (MS) has been widely proved as a predictor of cardiovascular disease, all-cause, and cardiovascular mortality in general population. But its effects on mortality and technique failure have not been well illustrated in peritoneal dialysis (PD) patients. We aimed to investigate the association of MS and clinical outcomes in Chinese continuous ambulatory PD (CAPD) patients. Methods: A single-center, prospective, observational cohort study was conducted in CAPD patients enrolled from September 1 to December 31, 2011, and followed up until December 31, 2016. Demographic, clinical, biochemical and anthropological data were collected. The relationships between MS and mortality and technique failure were assessed using Kaplan-Meier and Cox Regression Survival Functions. Results: A total of 511 patients were enrolled. The baseline mean age was 48.4 ± 14.4 years, 282 patients (55.2%) were male, and 130 patients (25.4%) were diabetic. In total, 213 patients (41.7%) met the diagnostic criterion of MS. During a median of 4.4 years (interquartile range 2.3-5.3 years) follow-up period, 114 patients died, of whom, 65 patients (48%) died in MS group versus 49 patients (30%) in non-MS group. Patients who died tended to be older, higher in inflammation markers and with poorer nutritional state. Kaplan-Meier Survival Functions found patients with MS had a significant rising of all-cause mortality (log-rank test = 12.811, p < 0.001) and cardiovascular mortality (log-rank test = 14.529, p < 0.001) in all patients, and a significant rising of cardiovascular mortality (log-rank test = 4.486, p = 0.034) in non-diabetic patients. After adjusting for confounders, Cox Regression showed that MS was significantly associated with higher cardiovascular mortality in all patients (hazard ratio [HR] 2.21, 95% CI 1.12-4.36, p = 0.022) and in non-diabetic patients (HR 2.60, 95% CI 1.07-6.35, p = 0.036), but it has no significant effect on technique failure. Conclusion: In CAPD patients, MS predicted mortality, especially cardiovascular mortality. No relationship was found between MS and technique survival.